Micellar self-assembly of perfectly sequence-defined recombinant resilin-like/elastin-like block copolypeptides - Weitzhandler, Isaac (Biomacromolecules, 2017)
This paper reports the synthesis of perfectly sequence defined, monodisperse diblock copolypeptides of a hydrophilic elastin-like polypeptide block and a hydrophobic resilin- like polypeptide block and characterization of their self-assembly as a function of structural parameters by light scattering, cryo-TEM, and small-angle neutron scattering. A subset of these diblock copolypeptides exhibit LCST and UCST phase behavior and self-assemble into spherical or cylindrical micelles. Their morphology is dictated by their chain length, degree of hydrophilicity and hydrophilic weight fraction of the ELP block. We find that: (1) independent of the length of the corona forming ELP block there is a minimum threshold in the length of the RLP block below which self-assembly does not occur, but that once that threshold is crossed, (2) the RLP block length is a unique molecular parameter to independently tune self-assembly; and (3) increasing the hydrophobicity of the corona-forming ELP drives a transition from spherical to cylindrical morphology. Unlike the self-assembly of purely ELP based block copolymers, the self-assembly of RLP-ELPs can be understood by simple principles of polymer physics relating hydrophilic weight fraction, polymer-polymer and polymer-solvent interactions to micellar morphology, which is important as it provides a route for the de novo design of desired nanoscale morphologies from first principles.